Joint Beamforming, Terminal Scheduling, and Adaptive Modulation with Imperfect CSIT in Rayleigh Fading Correlated Channels with Co-channel Interference - Robles, Ramiro (2017)
The Second International Conference on Advances in Signal, Image and Video Processing - from Sensing to Applications (SIGNAL 2017). 21 to 25, May, 2017, 5Gsignalwave. Barcelona, Spain.